IMPLEMENTASI SISTEM CERDAS PEMILAH SAMPAH LOGAM, ORGANIK DAN ANORGANIK OTOMATIS DENGAN METODE FUZZY SUGENO ORDE NOL BERBASIS INTERNET OF THINGS (STUDI KASUS: BANK SAMPAH KAMPUNG BARU) - Ajib Bahauddin; Munawaroh (Journal of Research and Publication Innovation, 2025)
Efforts to maintain health and environmental cleanliness can be done through proper waste management in the community. One important step is to reducing the production of waste that is difficult to recycle. An innovative approach in addressing the waste problem is through the Waste Bank program, where recyclable waste can be resold, thus helping to reduce the production of hard-to-recycle waste. waste that can still be recycled can be resold, thereby helping to reduce the adverse impact on the environment. One example of the implementation of this system system is the Kampung Baru Waste Bank located in Pondok Cabe Village. Research This research develops a prototype for automatic waste sorting at the Kampung Baru Garbage Bank, using the Kampung Baru, using inductive proximity sensors and raindrop sensors. The design design considers the aspects of long-term development and flexibility to adopt the latest technological innovations. The trial and implementation of an Internet of Things (IoT)-based system for sorting metal, organic and inorganic waste has met the planned specifications. Monitoring of waste capacity can be done in real-time thanks to the integration of Arduino Wifi R3 as a microcontroller in the IoT network. The system uses the zero-order Sugeno fuzzy method which was chosen for its simplicity of implementation in a microcontroller. The success of this system proves the effectiveness of the combination of IoT technology with the zero-order sugeno fuzzy method in waste sorting automation. The results of this study show that the application of IoT in Kampung Baru Waste Bank can ease the burden on Waste Bank administrators in sorting waste.